Inverse Boundary Value Problem for the Magnetohydrodynamics Equations - Lianhua He; Zhong Tan (Journal of Function Spaces)
In this paper, we consider the stationary magnetohydrodynamics (MHD) equations in a bounded domain of ℝd d=2,3 with viscosity and magnetic diffusing. By the linearization technique, we prove that the uniqueness of viscosity function and magnetic diffusing function in the MHD equations is determined from the knowledge of the Cauchy data measured on the boundary.